Reading Lolita in Tehran a memoir in books - Nafisi, Azar (Random House, 2004)
Prof. Nafisi resigned from her job as professor of English Literature at a university in Tehran in 1995 due to repressive government policies. For the next 2 years, until she left Iran, she gathered 7 young women, former students, at her house every Thursday morning to read and discuss works of Western literature forbidden by the new regime. They used this forum to learn to speak freely, not only about literature, but also about the social, political, and cultural realities of living under strict Islamic rule.